METHODS OF DETERMINING THE LEVELS OF FORMATION OF STUDENTS' AESTHETIC WORLD VIEW - Suyarova Feruza (American Journals, 2023)
This article talks about the methods of determining the levels of formation of students' aesthetic outlook. Based on pedagogical data, the author analyzed the problem based on existing scientific literature and methods of determining the levels of formation of the aesthetic outlook of students.
Keywords: Pupils, aesthetic outlook, degree of formation, methods of identification.